The persuasive function of the blood of Jesus in Matthew 26:28 - M.J. Nel (Acta Theologica)
In Matthew 26:28, Jesus links his blood to the forgiveness of sins during the Last Supper. Matthew’s reference to “the blood of the covenant” in 26:28 is an allusion to Exodus 24:8, symbolising Jesus as a sacrificial offering that renews the covenant with God. References to Zechariah 9:9-13 and Isaiah 53:12 further link Jesus’ death to the renewal of the covenant. For Matthew, the forgiveness of sins is a penultimate step for the renewal of the covenant that is the ultimate goal of Jesus’ death. This article also contrasts Matthew’s intertextual approach in the passion narrative with that of his prologue. It is argued that the shift towards allusions and echoes when explaining Jesus’ death aligns with Matthew’s strategy that can be described as a kaleidoscopic atonement theory, in which he weaves various Old Testament themes together to construct a comprehensive theory of atonement in Matthew 20:28 and 26:28.